The Effect of Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) on the Stock Price of PT. Astra Internasional Tbk (Years 2013-2021) - Bayhaqiy, Ahmad Zahir; Deny Yudiantoro; Amalia Nuril Hidayati (HM Publisher, 2022)
This study aims to analyze the effect of Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) on the stock price of PT.Astra Internasional Tbk. The type of research used is causal research, while the data source of this research is secondary data. Researchers used financial data for the period 2013-2021 which was analyzed with SPSS 21.0. The data analysis method used is multiple linear regression analysis and hypothesis testing using t test, f test and coefficient of determination. The results of this study are partially ROA and EPS have no significant effect on stock prices, but simultaneously ROA, ROE, and EPS have a significant effect on stock prices. ROA, ROE, and EPS are ratios that show the company's ability to generate profits, which is one way to know the company's performance.